2010
DOI: 10.1071/an09211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary nitrate on fermentation, methane production and digesta kinetics in sheep

Abstract: The effects of dietary nitrate on DM digestion, rumen volatile fatty acid concentrations, microbial protein outflow, rumen water kinetics, and methane production were studied. Eight rumen-cannulated sheep were acclimated to a diet consisting of chaffed oaten hay supplemented with either 4% KNO3 or 0% KNO3 but made iso-nitrogenous by the addition of urea. Nitrate supplementation did not affect blood methaemoglobin concentration, DM intake, whole tract or ruminal DM digestibility and the sheep appeared healthy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
87
4
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 14 publications
22
87
4
8
Order By: Relevance
“…In groups of grazing ruminants, methane release rate follows a diurnal biphasic pattern with peak emission rates in mid-morning and again in late afternoon (Figure 1a and b). These emission peaks probably coincide with bouts of more intensive grazing known to occur in the morning and at night (Champion et al, 1994).Emission rate rises and falls after eating (Mathers and Walters, 1982;Nolan et al, 2010) in response to substrate supply. Eating changes the ruminal contraction frequency in sheep and (less so) in cattle (Waghorn and Reid, 1983).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…In groups of grazing ruminants, methane release rate follows a diurnal biphasic pattern with peak emission rates in mid-morning and again in late afternoon (Figure 1a and b). These emission peaks probably coincide with bouts of more intensive grazing known to occur in the morning and at night (Champion et al, 1994).Emission rate rises and falls after eating (Mathers and Walters, 1982;Nolan et al, 2010) in response to substrate supply. Eating changes the ruminal contraction frequency in sheep and (less so) in cattle (Waghorn and Reid, 1983).…”
mentioning
confidence: 88%
“…Emission rate rises and falls after eating (Mathers and Walters, 1982;Nolan et al, 2010) in response to substrate supply. Eating changes the ruminal contraction frequency in sheep and (less so) in cattle (Waghorn and Reid, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on sheep (Sar et al, 2004;Nolan et al, 2010;van Zijderveld et al, 2010) and cattle (van Zijderveld et al, 2011a and2011b;Hulshof et al, 2012) has shown promising results with nitrates decreasing enteric CH 4 production by up to 50%. Nitrates may be particularly attractive in developing countries where forages contain negligible levels of nitrate and insufficient CP for maintaining animal production.…”
mentioning
confidence: 99%
“…The reduction of nitrate to nitrite and then to ammonium provides an energetically more favourable route for disposal of metabolic hydrogen produced during fermentation of feed carbohydrates in the rumen than the production of CH 4 . Although nitrate has been shown in many studies to reduce CH 4 emissions from ruminants (Nolan et al, 2010;Van Zijderveld et al, 2010 andHulshof et al, 2012;Li et al, 2012), the potential for its use has been hindered due to the toxicity of the intermediate product (nitrite). In the rumen, microbes rapidly reduce nitrate to nitrite and then reduce nitrite to ammonia.…”
mentioning
confidence: 99%